Der Deutsche Orden und seine pastorale Tätigkeit in der Ballei Österreich bis zur Krise im 16. Jahrhundert - Mlinar, Janez (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2019)
The Teutonic Order and Its Pastoral Work in the Bailiwick of Austria up to the Crisis in the 16th Century The Teutonic Order began to acquire land tenure in the Eastern Alps soon after its formation. After the Order’s structure had been established the Order also acquired rights of patronage over individual parishes in the 13th century. Up to the end of the Middle Ages the Order exercised the rights of patronage over seven parishes in the Bailiwick of Austria. Initially, however, pastoral work was not the Order’s main pursuit within the bailiwick; parishes served predominantly as the Order’s additional source of income. In the case of Velika Nedelja (Großsonntag) and Bela Krajina (White Carniola) the Teutonic Order had also a political function. The Order was tasked with the political, economic, and ecclesiastical integration of an area that did not become an integral part of the Holy Roman Empire before the 12th and early 13th century. From the 14th century onwards the Order intensified its pastoral activities, which coincides with the increase in the number of priests among its members.